The Trend of Halal Cosmetics Supply Chain Research in a Decade: A Systematic Review and Bibliometric Analysis - WAN MARHAINI WAN OMAR; NURZALIKHA AIMI MOHD SUBRI; MOHD HAFIZ ZULFAKAR (Information Management and Business Review, 2024)
The Halal cosmetics sector has risen in recent years, and it has received attention from academics and practitioners. Prior works on halal studies have examined food and beverage, but not the supply chain of halal cosmetics. This study aims to explore the distributions and trends of the halal cosmetics supply chain and to identify the gap in this research domain. The integrated systematic literature review and bibliometric analysis were employed to gain insight and evaluate the literature of this study. Based on the reviewed articles, the number of published halal cosmetics supply chain studies is limited. Data were obtained from the Scopus database, resulting in a limited dataset of 58 articles published between 2012 and 2023. Several tools and software were utilized for data extraction and analysis, including Publish or Perish, Excel Spreadsheet, and VOS Viewer. Co-citations analysis and co-words analysis were used to map the trends of publications and distinguish current research potentials. The findings reported the top authors of this research area, the main sub-research areas, and the most cited articles. In addition, new research directions in the realm of halal cosmetics supply chains were offered. Future academics could investigate new study clusters of the halal cosmetics supply chain empirically.